Incentives facing UK-listed companies to comply with the risk reporting provisions of the UK corporate governance code ‐ Abstract of the London Discussion. (13th March 2017) - Unknown
Abstract : This abstract relates to the following paper:P. Klumpes, C. Ledlie, F. Fahey, G. Kakar andS. Styles Incentives facing UK-listed companies to comply with the risk reporting provisions of the UK corporate governance code.British Actuarial Journal . doi:10.1017/5135732/716000180